El Metro de Santiago - Morales, Sergio (Revista EURE - Revista de Estudios Urbano Regionales, 1988)
This article spans on the historical background, construction and operation of Santiago de ChileÍ€™s metropolitan railway, also dealing with its main impacts. A review is made of the metroÍ€™s insertion in the urban transportation supply and its impact on the NationÍ€™s finance.